Dances with Sheep The Quest for Identity in the Fiction of Murakami Haruki - Strecher, Matthew (Michigan Monograph Series in Japanese Studies, 2020)
"As a spokesman for disaffected youth of the post-1960s, Murakami Haruki has become one of the most important voices in contemporary Japanese literature, and he has gained a following in the United States through translations of his works. In Dances with Sheep, Matthew Strecher examines Murakami's fiction-and, to a lesser extent, his nonfiction-for its most prevalent structures and themes. Strecher also delves into the paradoxes in Murakami's writings that confront critics and casual readers alike. Murakami writes of "serious" themes yet expresses them in a relatively uncomplicated style that appeals to high school students as well as scholars; and his fictional work appears to celebrate the pastiche of postmodern expression, yet he rejects the effects of the postmodern on contemporary culture as dangerous. Strecher's methodology is both historical and cultural as he utilizes four distinct yet interwoven approaches to analyze Murakami's major works: the writer's "formulaic" structure with serious themes; his play with magical realism; the intense psychological underpinnings of his literary landscape; and his critique of language and its capacity to represent realities, past and present. Dances with Sheep links each of these approaches with Murakami's critical focus on the fate of individual identity in contemporary Japan. The result is that the simplicity of the Murakami hero, marked by lethargy and nostalgia, emerges as emblematic of contemporary humankind, bereft of identity, direction, and meaning. Murakami's fiction is reconstructed in Dances with Sheep as a warning against the dehumanizing effects of late-model capitalism, the homogenization of the marketplace, and the elimination of effective counterculture in Japan."